Evaluation of Etiological Causes in Children with Symptomatic Hematuria - Ağar, Buket Esen; Kara, Aslıhan; Gürgöze, Metin Kaya; Bulut, Leyla (My University, 2022)
Hematuria is an important and common symptom of urinary system pathologies in children, and careful evaluation is required for its definitive diagnosis. This study aimed to determine the demographic and clinical characteristics and etiological causes of patients who applied to our pediatric nephrology clinic with hematuria. In this study, the record of 434 patients who were followed up in our clinic for macroscopic and/or microscopic hematuria were evaluated retrospectively. Demographic data, clinical findings, laboratory and imaging examinations, and final diagnosis of the patients were recorded. Out of 434 patients with hematuria, 239 (55%) were males and 195 (45%) females. Of the patients, 291 (67%) had macroscopic hematuria, and 83 (19.1%) had glomerular hematuria. Non-glomerular causes were found in 80.9%, with a significantly higher rate. Most of the causes of non-glomerular hematuria were urinary tract infection and renal stones. Acute post-streptococcal glomerulonephritis (APSGN) was found to be responsible for the majority of glomerular diseases. This study shows that most pathologies that may cause hematuria can be detected with a detailed history, careful physical examination, and simple laboratory tests.
Keywords: Mikrobiyoloji; Üroloji ve Nefroloji; Acil Tıp; Kulak; Burun; Boğaz; Pediatri